A novel strategy for the synthesis of self-healing capsule and its application. (8th February 2019) - Sun, Tao; Shen, Xuejing; Peng, Chong; Fan, Hongyu; Liu, Minjing; Wu, Zhanjun
Abstract: Phenol formaldehyde (PF) resin capsules containing dicyclopentadiene (DCPD) as core materials are rationally designed and fabricated. The synthesis consists of preparation of polystyrene (PS) sphere, PF coating on PS sphere, followed by removal of PS core, amination modification and importing of DCPD. Solution phase switchable transport trough PF shell layer is key for the synthesis of DCDP@PF capsules. The resultant DCDP@PF capsules have a diameter of ∼500 nm, shell thickness of ∼50 nm, and core content of ∼45 wt%. The results show that DCDP@PF capsules have outstanding thermal stability with initial evaporation temperature (defined at 5% of weight loss), increased by ∼30 °C compared with that of pure DCPD, and good resistance to acetone. Preliminary results indicated that the prepared DCPD@PF capsules can effectively improve the mechanical properties of epoxy matrix as well as impart it self-healing properties. When 15 wt% DCPD@PF capsules were introduced into epoxy matrix, 81.4% increment in fracture toughness, 26.6% increment in tensiles strength and 91.8% recovery in fracture toughness can be obtained. This work provides a new insight into the investigation of the fabrication of self-healing capsules.